Patient-specific Guides Using 3-dimensional Reconstruction Provide Accuracy and Reproducibility in Reverse Total Shoulder Arthroplasty - Jong Pil Yoon; Dong Hyun Kim; Jae Wook Jung; Chang-Hwa Lee; Seunggi Min; Hyun Joo Lee; Hee-June Kim (Clinics in Shoulder and Elbow, 2019)
Background We aimed to evaluate whether the use of our novel patient-specific guide (PSG) with 3-dimensional reconstruction in reverse total shoulder arthroplasty (RTSA) would allow accurate and reliable implantation of the glenoid and humeral components. Methods 20 fresh-frozen cadaveric shoulders were used. The PSG group (n=10) and conventional group (n=10) was evaluated the accuracy and reproducibility of implant positioning between before and after surgery on the computed tomography image. Results The superoinferior and anteroposterior offset in the glenoid component were 0.42 ± 0.07, 0.50 ± 0.08 in the conventional group and 0.45 ± 0.03, 0.46 ± 0.02 in the PSG group. The inclination and version angles were -1.93° ± 4.31°, 2.27° ± 5.91° and 0.46° ± 0.02°, 3.38° ± 2.79°. The standard deviation showed a smaller difference in the PSG group. The anteroposterior and lateromedial humeral canal center offset in the humeral component were 0.45 ± 0.12, 0.48 ± 0.15 in the conventional group and 0.46 ± 0.59 (p=0.794), 0.46 ± 0.06 (p=0.702) in the PSG group. The PSG showed significantly better humeral stem alignment. Conclusions The use of PSGs with 3-dimensional reconstruction reduces variabilities in glenoid and humerus component positions and prevents extreme positioning errors in RTSA.